The Determination of the Relationship between Somatotypes and Speed of Sub-Elite Athletes - MARANGOZ, İrfan (Asian Journal of Education and Training, 2018)
This study aims to analyze the relationship between somatotypes and speed of 180 male sub-elite athletes aged between 18 and 25. Athletes were divided into two categories as balanced group (balanced somatotype groups) and randomly selected groups (groups outside balanced somatotypes groups) based on their somatotype structures. The arithmetic means and standard deviations of groups are (n=30) 21.95±2.80 years of age, height 168.40±2.62 cm, weight 69.20±5.26 kg in balanced endomorph group, (n=30) 21.60±3.15 years of age, height 170.25±6.39 cm, weight 67.25±6.09 kg in balanced mesomorph group, and (n=30) 20.40±1.46 years of age, height 175.10±5.02 cm, and weight 60.05±5.09 kg in balanced ectomorph group. On the other hand, the same values are (n=30) 21.35±2.30 years of age, height 160.10±2.20 cm, and weight 69.30±5.70 kg in random endomorph group, (n=30) 21.36±2.40 years of age, height 169.24±2.21 cm and weight 65.40±3.25 kg in random mesomorph groups, and (n=30) 20.50±1.85 years of age, height 176.15±3.30 cm and weight 70.10±4.45 kg in random ectomorph group. The measurement data were analyzed using SPSS 2.0 package program for Windows. Somatotype calculations were done in SOMATOTURK Calculation Program. The statistical analysis demonstrated that a highly positive significant correlation (p˂0.001) was found between balanced somatotype groups (balanced endomorph, mesomorph and ectomorph) and randomly selected somatotype groups (random endomorph, mesomorph and ectomorph).